Analysis of the Influence of the Distribution and Development of Soil Caves on the Stability of High-Voltage Transmission Tower Foundations - Yingbo Zhou; Li Zhou; Zhiqiang Duan; Fangchao Ke; Huan Liu (Advances in Civil Engineering)
As a kind of concealed flawed geology, karst geology easily forms soil caves, which may have a negative effect on adjacent transmission tower foundations. Since soil caves are continuously developed when surface water flows through soil, or groundwater levels fluctuate, the effect of soil caves on transmission lines in power transmission engineering needs to be investigated. In this paper, combined with an engineering case in western Hubei, first, FLAC3D finite element software is used to analyze the influence of a single underground soil cave during continuous development and expansion on 500 kV transmission towers. Considering the maximum allowable tilt value of the tower foundation, the stress state and deformation of the soil around the foundation are monitored during the calculation and analysis, and the maximum allowable radius of the soil cave in different positions is obtained. For example, the development radii of soil holes are 1.5 m, 2 m, and 2.5 m for burial depths of 7 m and 8 m, 9 m, and 10 m and 11 m, respectively, and the development radius of soil holes with a burial depth of 12 m and below can reach the maximum value of 3 m under actual working conditions. Then, the results of two simplified models of columnar and spherical development of the soil cave are compared, and it is found that columnar development is more in line with the actual situation. Finally, under the condition of a close-range double soil cave distribution, the influence of the size, depth, and gap between the two caves on the tower foundation is simulated. This study can provide references for the safe operation of transmission towers and the assessment of possible disasters in karst areas.